Fluoride and caries prevention: a scoping review of public health policies - Veneri, Federica; Vinceti, Silvio Roberto; Filippini, Tommaso (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. Dental caries is the most common infectious disease, affecting approximately 60 to 90% of the world population, especially young children, and disadvantaged communities. Due to the extremely high prevalence and the significant negative impact on general health, well-being, and quality of life it is considered a global public health problem. Despite the improvement of policies to promote oral health care in the past decades, dental caries is still a healthcare challenge, characterized by increasing disparities among different social groups between and within countries. Fluoride-based prevention of dental caries is a cost-effective approach, that has been implemented since 1940’s. It includes systemic and topical administrations, through community-based or individual programs. Preventive interventions should be tailored to individual and community caries risk assessment and estimate of cumulative fluoride intake, in order to maximize the preventive effect and avoid the risk of potential adverse effects associated with excessive fluoride exposure. Regulation of public health policies plays a major role in this context.Study design. Scoping review.Methods. The aim of this scoping review was to report an overview of current guidelines regarding fluoride-based preventive strategies for dental caries and relevant policies on the matter, as well as to address current issues related to public health aspects of dental caries prevention. We searched for the relevant literature on the matter, focusing on policy documents, such as recommendations, position papers and guidelines, issued from the major scientific and regulatory institutions involved in oral health promotion and on publications concerning relevant aspects of public health law.Results. Prevention of dental caries through fluoride can rely on topical fluorides for home-use (toothpastes and mouthrinses), professionally applied topical fluorides (gels, varnishes, silver diamine fluoride, fluoride-releasing restorative materials and sealants), fluoride supplements (tablets and drops), and community-based strategies (community water fluoridation, fluoridated salt and milk). Current relevant guidelines for all these preventive aids are outlined in the paper. A significantly greater preventive effect of topical fluorides has been widely established in the recent past, as compared to systemic effects. Furthermore, increasing concerns have emerged on potential adverse effects on general health associated with early and excessive systemic exposure to fluoride, especially for children, supported by recent meta-analyses. Also, community water fluoridation has raised significant aspects of relevance for health law and policies. In a public health perspective, healthcare policymakers should tackle social iniquities by promoting information and oral health literacy, through community and school-based programs, ensuring access to early dental visits and basic dental care and improving availability and affordability of fluoride topical products.Conclusions. Fluoride-based prevention can provide a simple and cost-effective approach to reduce the incidence of dental caries and the associated social burden. Among fluoride-based preventive strategies, systemic community-based administration of fluoride should be considered with great caution, due to the unfavorable risk-benefit ratio currently established. Topical fluoridated products are generally preferred, given the optimal risk-benefit ratio. Further efforts must be made to identify and tackle the barriers to dental caries prevention and related social iniquities from a public health perspective. Policies and laws on oral health should promote access to caries prevention with targeted comprehensive strategies.